Implementation of Multicultural-Based Social Science Learning and the Influential Factors: (A Case Study of PGSD Students at Langlangbuana University) - Sri Rohartati; Babang Robandi (Studies in Learning and Teaching, 2023)
The goal of this study was to learn about the implementation of multicultural-based social science learning for elementary school teacher education (PGSD) students at Universitas Langlangbuana, as well as the supporting and inhibiting factors that influence multicultural-based social science learning implementation.This is a qualitative study that intends to reveal numerous aspects about occurrences, phenomena, and social symptoms in elementary school teacher education students at Universitas Langlangbuana.The implementation of multicultural-based IPS learning and the supporting and inhibiting elements in the implementation of multicultural-based social science learning courses are the topic of this study. The implementation of multicultural-based social science learning as a means of preventing radicalism comprises three stages: planning, execution, and evaluation. Religious, ethnic, and cultural aspects, as well as support from friends and the surrounding community, all play a role in the implementation of multicultural-based social science learning. Meanwhile, internal and external issues are impeding the use of multicultural-based IPS learning. Internal issues include students and the lecture process in class, while external factors include the internet's impact, non-educational television shows such as brawls, and group tasks that are rarely completed with other students.